2014
DOI: 10.2337/dc13-2738
|View full text |Cite
|
Sign up to set email alerts
|

HDL-C and HDL-C/ApoA-I Predict Long-Term Progression of Glycemia in Established Type 2 Diabetes

Abstract: OBJECTIVELow HDL cholesterol (HDL-C) and small HDL particle size may directly promote hyperglycemia. We evaluated associations of HDL-C, apolipoprotein A-I (apoA-I), and HDL-C/apoA-I with insulin secretion, insulin resistance, HbA 1c , and long-term glycemic deterioration, reflected by initiation of pharmacologic glucose control. RESEARCH DESIGN AND METHODSThe 5-year Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) study followed 9,795 type 2 diabetic subjects. We calculated baseline association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 40 publications
6
41
0
Order By: Relevance
“…We also observed significant changes in fat mass and waist circumference similar in magnitude to those observed in the Look AHEAD trial [43]. The inverse relationship between changes in A1c and serum HDL-C shown in the PANDA intervention has been reported by others [44,45] but is not as well established as that between A1c and BMI and is not seen in all studies [46,47]. However, a prospective trial demonstrated that low baseline HDL-C predicted more rapid long-term progression of T2D [46].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We also observed significant changes in fat mass and waist circumference similar in magnitude to those observed in the Look AHEAD trial [43]. The inverse relationship between changes in A1c and serum HDL-C shown in the PANDA intervention has been reported by others [44,45] but is not as well established as that between A1c and BMI and is not seen in all studies [46,47]. However, a prospective trial demonstrated that low baseline HDL-C predicted more rapid long-term progression of T2D [46].…”
Section: Discussionsupporting
confidence: 81%
“…The inverse relationship between changes in A1c and serum HDL-C shown in the PANDA intervention has been reported by others [44,45] but is not as well established as that between A1c and BMI and is not seen in all studies [46,47]. However, a prospective trial demonstrated that low baseline HDL-C predicted more rapid long-term progression of T2D [46]. HDL-C promotes insulin secretion and protection from apoptosis of beta-cells [48], which may be related to HDL-C-mediated anti-oxidative and cellular cholesterol efflux activities [49].…”
Section: Discussionmentioning
confidence: 84%
“…The HDL-C/apoA-I ratio has been suggested to be a useful biomarker to estimate HDL particle size [26]. Smaller cholesterol-poor HDL particles are reflected by lower HDL-C levels and HDL-C/apoA-1 ratios [26,27]. Alterations in HDL size and cholesterol content may reflect reduced efficacy of reverse cholesterol transport [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have only reported an outcome based on progression to glucoselowering medications (i.e. time to initiation of non-insulin glucose-lowering medication, failure of monotherapy or time to insulin therapy) [1,[3][4][5][6][7][8][9]. In these studies, younger age at diagnosis and insufficient beta cell function were consistently associated with faster progression of diabetes.…”
Section: Introductionmentioning
confidence: 99%